Analysis of Buying, Selling, and Leasing Virtual Land in the Metaverse: A Perspective from Sharia Economic Law - Muhamad Izazi Nurjaman; Sofian Al-Hakim; Iwan Setiawan; Mualimin Mochammad Sahid (Faculty of Sharia at Sultan Agung Islamic University in Indonesia, 2024)
Non-Indexed Publication